Implementasi Pengajuan Surat Perintah Membayar (SPM) pada Dinas Perhubungan Kabupaten Tulungagung (Universitas 17 Agustus 1945 Surabaya, 2023)
One of the crucial aspects of the public policy process is the implementation of public policy. In submitting a payment order (SPM) to the Tulungagung Regency Petrhubungan Office which is guided by Permendagri Number 77 of 2020. This study aims to find out how the implementation of permendagri number 77 of 2020 in submitting a payment warrant (SPM) and what factors are the obstacles. This research uses a type of qualitative method where researchers explore key instruments. Data Sources are used using interview techniques with the officials concerned. The results showed that the implementation of permendagri number 77 of 2020 in submitting a payment order (SPM) at the Tulungagung Regency Transportation Office was relatively good, but there were several factors that hindered it, namely communication that needed to be socialized, lack of human resources, and tendencies or dispositions that were not in accordance with their competence. The advice given is the need to hold socialization, increase resources that have dedication and recruitment of personnel in accordance with their competencies.